Effects of Infusion and Storage on Antioxidant Activity and Total Phenolic Content of Black Tea - Chang, Min-Yun; Lin, Yin-Yi; Chang, Yu-Chia; Huang, Wen-Ying; Lin, Wen-Shin; Chen, Cheng-You; Huang, Shu-Ling; Lin, Yung-Sheng (Applied sciences, 2020)
This study determined antioxidant activity in terms of the 1,1-Diphenyl-2-picrylhydrazyl (DPPH) scavenging ability and total phenolic content of black tea under different infusion and storage conditions. High performance liquid chromatography analysis identified caffeine, (−)-epigallocatechin, (−)-epicatechin-3-gallate, (−)-epigallocatechin-3-gallate and (−)-gallocatechin-3-gallate in the tea sample. The water–tea leaves weight ratio did not affect the DPPH scavenging ability. However, infusion temperature affected the DPPH scavenging activity and the total phenolic content. In the present study, the 50% inhibitory concentrations (IC50) for DPPH of black tea infused at 60 to 100 °C ranged from 100.0 ± 13.7 to 28.4 ± 4.8 μg/mL. The total phenolic content of black tea steeped at 60 to 100 °C ranged from 50.4 ± 5.2 to 178.6 ± 16.4 mg gallic acid equivalent/g dry leaf. Black tea exhibited increased antioxidant activity when the infusion temperature was increased. Regarding short-term storage, the DPPH scavenging ability and total phenolic content of black tea did not significantly change within 15 days. This result was consistent for storage temperatures of 4, 9, and 25 °C.